Spatiality and Symbolic Expression - Richardson, Bill. author. aut Link
XI, 250 p.
Keywords: In this volume, scholars from a wide range of fields within the humanities explore the links between space and place and their relation to cultural expression. This collection shows that a focus on the spatial can help elucidate important facets of symbolic expression and cultural production, whether it be literature, music, dance, films, or art.